Ke-Kriya-an pada Arsitektur Jawa - Hardiyati Hardiyati; Anita Dianingrum (Universitas Sebelas Maret Surakarta, 2021)
Development of unlimited information resulting in the loss of the diversity of architectural identity of place. Contemporary architecture develops without control and without clear concept seeds. Craftsmanship is always attached to art because in the final result there is a content of art, even though the meaning of art is always being discussed and always developing. Javanese house architecture has three important things, namely the relationship of Jiwa Cipta / wastu, resources / kalang and form / wewangunan, which are the totality of architecture. The purpose of this research is to describe the understanding of